2022
DOI: 10.48550/arxiv.2203.12553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DSRC & C-V2X Comparison for Connected and Automated Vehicles in Different Traffic Scenarios

Abstract: Researches have been devoted to making connected and automated vehicles (CAVs) faster in different traffic scenarios. By using C-V2X or DSRC communication protocol, CAVs can work more effectively. In this paper, we compare these two communication protocols on CAVs in three different traffic scenarios including ramp merging, intersection, and platoon brake. It shows there is a trade-off between communication range and interval when leveraging C-V2X or DSRC for CAVs. The result can help support further applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To enable these activities, two sorts of technologies are used. The first one pertains to connectivity, and features many developed standards such as DSRC and C-V2X [137]. Secondly, we find AI technology and its branches (see Section II) dedicated to the automation part.…”
Section: B Connected and Autonomous Vehicles 1) Motivationmentioning
confidence: 99%
“…To enable these activities, two sorts of technologies are used. The first one pertains to connectivity, and features many developed standards such as DSRC and C-V2X [137]. Secondly, we find AI technology and its branches (see Section II) dedicated to the automation part.…”
Section: B Connected and Autonomous Vehicles 1) Motivationmentioning
confidence: 99%
“…9. According to research, C-V2X can offer more coverage (as shown in the picture), improved dependability, better support for quality of service (QoS), 360°non-line-of-sight (NLOS) awareness, and higher capacity than DSRC [46]. Both RATs are capable of supporting basic safety use cases, such as traffic light information and emergency vehicle notifications, road work, and emergency brake warnings, with end-to-end latency needs of about 100 milliseconds under conditions of moderate vehicular congestion.…”
Section: ) C-v2x and Dsrcmentioning
confidence: 99%
“…The results demonstrate that 802.11bd outperformed its predecessor, 802.11p, in multiple V2X performance metrics and provide valuable observations and experience in operating the NGV standard. However, as a typical cyber-physical system, the existing study [25] has already verified that the performance of V2X will be affected by traffic scenarios. Most prior simulation-based studies have overly simplified the test scenarios to one-to-one or one-tomany linear arrays, thus overlooking the influence of intricate and dynamic large-scale traffic environments on the communication performance of the IEEE 802.11bd standard.…”
Section: Introductionmentioning
confidence: 99%